Twenty-Five Years of Intracranial Pressure Monitoring After Severe Traumatic Brain Injury: A Retrospective, Single-Center Analysis. Issue 1 (23rd November 2018) - Donnelly, Joseph; Czosnyka, Marek; Adams, Hadie; Cardim, Danilo; Kolias, Angelos G; Zeiler, Frederick A; Lavinio, Andrea; Aries, Marcel; Robba, Chiara; Smielewski, Peter; Hutchinson, Peter J A; Menon, David K; et al.
Abstract: BACKGROUND: Intracranial pressure (ICP) is a clinically important variable after severe traumatic brain injury (TBI) and has been monitored, along with clinical outcome, for over 25 yr in Addenbrooke's hospital, Cambridge, United Kingdom. This time period has also seen changes in management strategies with the implementation of protocolled specialist neurocritical care, expansion of neuromonitoring techniques, and adjustments of clinical treatment targets. OBJECTIVE: To describe the changes in intracranial monitoring variables over the past 25 yr. METHODS: Data from 1146 TBI patients requiring ICP monitoring were analyzed. Monitored variables included ICP, cerebral perfusion pressure (CPP), and the cerebral pressure reactivity index (PRx). Data were stratified into 5-yr epochs spanning the 25 yr from 1992 to 2017. RESULTS: CPP increased sharply with specialist neurocritical care management ( P < 0.0001) (introduction of a specific TBI management algorithm) before stabilizing from 2000 onwards. ICP decreased significantly over the 25 yr of monitoring from an average of 19 to 12 mmHg ( P < 0.0001) but PRx remained unchanged. The mean number of ICP plateau waves and the number of patients developing refractory intracranial hypertension both decreased significantly. Mortality did not significantly change in the cohort (22%). CONCLUSION: We demonstrate the evolving trends in neurophysiological monitoring over the past 25 yr from a single, academic neurocritical care unit. ICP and CPP were responsive to the introduction of an ICP/CPP protocol while PRx has remained unchanged. Graphical Abstract: